51.1k views
5 votes
FOR 100 POINTS!!!!!!!!!!!

Solve the equation.


3(4x + 4) = 2(5x + 9) - 12

2 Answers

0 votes

Answer:

X=-3

Explanation:

Isolate x on one side of the equation.

DISTRIBUTIVE PROPERTY

A(B+C)=AB+AC

A(B-C)=AB-AC

3(4x+4) (First, expand.)

3*4x=12x

3*4=12

12x+12

2(5x+9)-12

2*5x=10x

2*9=18

10x+18

18-12=6

12x+12=10x+6

12x+12-12=10x+6-12 (Subtract 12 from both sides.)

6-12 (Solve.)

12-6=6

12x=10x-6

12x-10x=10x-6-10x (Subtract 10x from both sides.)

12x-10x (Solve.)

12x-10x=2x

2x=-6

2x/2=-6/2 (Then, divide by 2 from both sides.)

-6/2 (Solve.)

-6/2=-3

x=-3

As a result, the final answer is x=-3.

User Ramesh Yankati
by
4.6k points
4 votes

Answer:

x = -3

Explanation:

Step 1: Distribute

3(4x + 4) = 2(5x + 9) - 12

(3 * 4x) + (3 * 4) = (2 * 5x) + (2 * 9) - 12

12x + 12 = 10x + 18 - 12

Step 2: Combine like terms

12x + 12 = 10x + 6

Step 3: Subtract 10x from both sides

12x + 12 - 10x = 10x + 6 - 10x

2x + 12 = 6

Step 4: Subtract 12 from both sides

2x + 12 - 12 = 6 - 12

2x = -6

Step 5: Divide both sides by 2

2x / 2 = -6 / 2

x = -3

Answer: x = -3

User Richie Li
by
5.5k points